Transhabitat: topologias transorgânicas em arte e tecnologia - Camargo, Matheus Moreno dos Santos (2016)
The poetical research Transhabitat proposes other communicative ways of inhabiting in the context of Art and Technology. With the accomplishment of interactive installations, it problematizes the definition of topology from the concepts of cybrid proposed by Peters Anders (1997), and of transorganic, presented by Di Felice (2009). In the transorganic environments that were built, the spacial configurations are stablished through the informational flow and hybrid connections of the physical space and cyberspace, also named cybrids informations, whose observer-interactor connect autopoetically. These topologies are present in occasional diagrams, processes of virtualization and updating of the space surfaces, and are provided from the interaction between complex systems data in several scales, resulting in interactive images which connect the individual to the transorganic habitats through local actions interconnected by network. The generative topologies proposed in this research, by being constituted of layers of dynamic standard and transmutable surfaces generate spacial expansion with the inclusion of movements and possible times in the hyperspace, where the individuals interact in real time with the habitats proposed. In this way, Transhabitat is constituted by transorganic, interactive and connected habitats which aim at provoking spacial hybridisation in cybrids relations among individuals and environments, in an organism of data and flow of information.